Optimizing radiotherapy plans for cancer treatment with Tensor Networks. (16th June 2021) - Cavinato, Samuele; Felser, Timo; Fusella, Marco; Paiusco, Marta; Montangero, Simone
Abstract: We present a novel application of Tensor Network methods in cancer treatment as a potential tool to solve the dose optimization problem in radiotherapy. In particular, the intensity-modulated radiation therapy technique—that allows treating irregular and inhomogeneous tumors while reducing the radiation toxicity on healthy organs—is based on the optimization problem of the beamlets intensities that shall result in a maximal delivery of the therapy dose to cancer while avoiding the organs at risk of being damaged by the radiation. The resulting optimization problem is expressed as a cost function to be optimized. Here, we map the cost function into an Ising-like Hamiltonian, describing a system of long-range interacting qubits. Finally, we solve the dose optimization problem by finding the ground-state of the Hamiltonian using a Tree Tensor Network algorithm. In particular, we present an anatomical scenario exemplifying a prostate cancer treatment. A similar approach can be applied to future hybrid classical–quantum algorithms, paving the way for the use of quantum technologies in future medical treatments.